Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have a doubt respect to resolution of differential equations, for example if we have the family of circles $x^2+y^2=2cx$, deriving $$2x+2y\frac{dy}{dx}=2c$$, combining $$\frac{dy}{dx}=\frac{y^2-x^2}{2xy}$$ and replacing $\frac{dy}{dx}=-\frac{dx}{dy}$, then we have the differential equation $$\frac{dy}{dx}=\frac{2xy}{x^2-y^2}(*)$$ We cannot find the solution of the last differential equation by separation of variables, but if we use polar coordinates in $x^2+y^2=2cx$ we get $$(r\cos\theta)^2+(r\sin\theta)^2=2c(r\cos\theta)$$ and $r=2c\cos\theta$, then $$\frac{dr}{d\theta}=-2c\sin\theta$$ and then $$\frac{r d\theta}{dr}=-\frac{\cos\theta}{\sin\theta}$$

The solution of the last differential equation is $r=2c\sin\theta$, so the solution of the differential equation (*) is $x^2+y^2=2cy$. Then my question is: why the change of coordinates permit find the solution of the differential equation? This is an accident or exit a theorem about this? And if exits such theorem, what kind of differential equation can be solve by change of coordinates? Thanks.

share|improve this question
    
Somehow, you have gone from $x^2+y^2=2cx$ to $x^2+y^2=2cy$. –  Gerry Myerson Oct 21 '12 at 5:02
    
I'll add more information. –  José Ramírez Oct 21 '12 at 5:07
1  
You have added more information, but you have not resolved the contradiction. In the second line, you have $x^2+y^2=2cx$. Later, you have $x^2+y^2=2cy$. These are different. One of them has an $x$ where the other has a $y$. How can both of them be the solution, when they are manifestly not equal to each other? –  Gerry Myerson Oct 21 '12 at 5:23
    
@GerryMyerson: I think the problem is the step in which $$\frac{\mathrm{d}y}{\mathrm{d}x}=-\frac{\mathrm{d}x}{\mathrm{d}y}$$ –  robjohn Oct 21 '12 at 10:43
    
@robjohn, yes, that step looks highly problematical, especially since what has actually been done looks more like $dy/dx=-1/(dy/dx)$. –  Gerry Myerson Oct 21 '12 at 11:48
show 6 more comments

3 Answers

up vote 1 down vote accepted

Solving (*)

We can solve $(\ast)$ without changing to polar coordinates $$ \frac{\mathrm{d}y}{\mathrm{d}x}=\frac{2xy}{x^2-y^2}\tag{1} $$ which can be manipulated to $$ \frac{\mathrm{d}}{\mathrm{d}y}\frac{x^2}{y}=\frac{2x}{y}\frac{\mathrm{d}x}{\mathrm{d}y}-\frac{x^2}{y^2}=-1\tag{2} $$ Integrating $(2)$ yields $$ \frac{x^2}{y}=2c-y\tag{3} $$ For some $c$. Therefore, $$ x^2+y^2=2cy\tag{4} $$

Answer to the Question

A change of coordinate may make the solution more apparent, but the equation should be solvable in either coordinate system.

share|improve this answer
    
The equation $$\frac{dy}{dx}=\frac{2xy}{x^2-y^2}(*)$$ is ok, but you don't answer the main question. –  José Ramírez Oct 21 '12 at 19:52
    
The main question was: "why [does] the change of coordinates permit [us to] find the solution of the differential equation?" My answer was "A change of coordinate may make the solution more apparent, but the equation should be solvable in either coordinate system." –  robjohn Oct 21 '12 at 21:25
    
The original equation $x^2+y^2=2cx$ has nothing to do with $(\ast)$ as written. That is the point which was confusing to me, and possibly to Gerry Myerson. –  robjohn Oct 21 '12 at 21:28
add comment

You can use a substitution for the Bernoulli DE you obtain when considering $\frac{dx}{dy} = \frac{x^2 - y^2}{2xy}$

Edit: Notice $\frac{dx}{dy} = \frac{x^2 - y^2}{2xy} \Rightarrow x' - \frac{x}{2y} + \frac{y}{2x} = 0$, where $x'$ is obviously with respect to $y$

share|improve this answer
    
Could you be more expecific? That is not the exact form like here en.wikipedia.org/wiki/Bernoulli_differential_equation –  José Ramírez Oct 21 '12 at 4:50
    
It appears to be for $n=-1$ where $$ P(y)=\frac1{2y}\qquad\text{and}\qquad Q(y)=\frac x2 $$ –  robjohn Oct 21 '12 at 10:54
    
But i know the answer of this, the problem is about this equation $$\frac{dy}{dx}=\frac{2xy}{x^2-y^2}(*)$$ and change of coordinates, you don't answer the main question. –  José Ramírez Oct 21 '12 at 19:56
add comment

When you replace $\frac{dy}{dx}=-\frac{dx}{dy}$, you get

$$ \frac{dx}{dy}=-\frac{y^2-x^2}{2xy}= -\frac{y}{2x}+\frac{x}{2y} \rightarrow (1)\,. $$

It is easier to solve the differential equation (1). Let

$$u=\frac{x}{y} \implies x=yu \implies \frac{dx}{dy}=u+y\frac{du}{dy} \,. $$

Substituting back in $(1)$ gives,

$$ u+y\frac{du}{dy}= -\frac{1}{2u}+\frac{u}{2}\implies y\frac{du}{dy} =\frac{3u^2-1}{2u}\,. $$

Now, I think you can solve the last ode by the method of separation of variables to find $u$ as a function in $y$, then, substitute back $ u=\frac{x}{y} $.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.